Analysis of PVDF/AgNO3 conductive membrane. (2021) - Khanduri, Priya; Panwar, Varij; Mohanty, Sribidhya
Abstract: Polymer matrix is used in various flexible sensors and actuators. In order to enhance their conductivity and mechanical strength various fillers are added. AgNO3 acts as nanofiller which makes the polymer matrix conductive. This work is devoted to the study of the effect of AgNO3 filler. In this paper, we evaluate the dielectric constant, dissipation factor and conductive property of PVDF/AgNO3 for a frequency range varying between 20 Hz and 10 MHz. Impedance Analyser was used to measure variation in properties. This paper concludes that on adding 0.6 gm of AgNO3 to PVDF, the best results of conductivity, dissipation factor and dielectric constant can be configured. The Conductivity of the membranes was highly improved by AgNO3 content. The paper shows that by addition of AgNO3 the dissipation factor is also affected which make it suitable for Radar and Electromagnetic Shielding Applications. On addition of AgNO3 the ohmic resistance value also varies. This conductive membrane can be used in various applications of flexible and wearable sensors. The proposed membrane is providing optimization of the amount of adding AgNO3 to make it suitable for Conductive membrane.